ELECTROSURGICAL MICRONEEDLE VERSUS SCALPEL SKIN INCISIONS IN THE FACIAL REGION - Margarita Peneva; Andrijana Gjorgjeska; Vladimir Ginoski; Hristina Breshkovska; Roza Dzoleva Tolevska (Association of Medical Doctors Sanamed, 2018)
Objective: Electrosurgery is widely used in surgical procedures, but mainly for subcutaneous and deep layer dissections. The aim of this study was to clinically evaluate the results of routine use of electrosurgical microneedle in performing skin incisions in the facial regions. Material and methods: Eighty patients with both benign and malignant skin lesions in the facial regions undergoing surgery were enrolled in this study. In group A comprising 40 patients, cold steel surgical scalpel ?15 was used for the surgical procedure. Electrosurgical microneedle with 0.06 mm tip radius and generator unit KLS Martin Electrosurgical Unit ME MB 2 set on cutting mode, power 12 W was used for performing the surgery in group B including the same number of patients. Differences between incision time, excision time, blood loss and the wound related complications were evaluated. Results: The two groups did not significantly differ in the speed of incision and speed of excision although both the speed of incision and the speed of excision were found to be slightly faster in the electrosurgery group. There was significantly less blood loss in the electrosurgery group compared with the scalpel group.Statistical analysis did not confirm as significant the difference in complications between the two groups although most of the complications were associated with the patients operated with scalpel. Conclusion: Electrosurgery presents safe and effective way of work. In that manner, it is very important to choose the right generator unit's settings and the right type of electrode.
Keywords: surgical scalpel; electrosurgery; facial regions